2017
DOI: 10.3390/ijerph14080941
|View full text |Cite
|
Sign up to set email alerts
|

Grip Strength and Its Relationship to Police Recruit Task Performance and Injury Risk: A Retrospective Cohort Study

Abstract: Suitable grip strength is a police occupational requirement. The aim of this study was to investigate the association between grip strength, task performance and injury risk in a police population. Retrospective data of police recruits (n = 169) who had undergone basic recruit training were provided, including handgrip strength results, occupational task performance measures (consisting of police task simulations [SIM], tactical options [TACOPS] and marksmanship assessments) and injury records. Left hand grip … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
99
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 76 publications
(124 citation statements)
references
References 30 publications
8
99
6
Order By: Relevance
“…Grip strength has commonly demonstrated a positive significant relationship with marksmanship in previous research within the law enforcement population [3,22]. Conversely, this study found a significant but negative relationship to shooting performance.…”
Section: Fitness Measurescontrasting
confidence: 44%
See 4 more Smart Citations
“…Grip strength has commonly demonstrated a positive significant relationship with marksmanship in previous research within the law enforcement population [3,22]. Conversely, this study found a significant but negative relationship to shooting performance.…”
Section: Fitness Measurescontrasting
confidence: 44%
“…This study investigated the relationships between different fitness measures and different marksmanship scenarios within a population of police officers. The different marksmanship scenarios were designed to mimic different environments that officers may face while in the field [3,16,20,27]. There were varying relationships between individual fitness measures and marksmanship scenarios, with significant relationships between the shuttle run and static shooting, grip strength and the dynamic scenario, and leg/back strength and the positive identification scenario.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations